Analisis Implementasi Pengendalian Internal Pada Siklus Penjualan (Studi Kasus Pada PT Tunas Group Ridean Tbk) - Azahrah, Rosa; Rahmat, Kamaluddin; Okabrian, Soni (Politeknik Negeri Bengkalis, 2023)
The purpose of this research is to provide an overview of sales cycle implementation and internal control implementation in PT. TunasÂ Ridean Groupâ€™s sales cycle. The sales cycle analysis process is based on the Romney & Steinbart sales cycle model, and the internal control implementation analysis process is based on the COSO IC internal control framework. The research method used is a qualitative descriptive method with the Miles & Huberman model as the data analysis method. Data collection techniques include semi-structured interviews and literature studies. The informant collection technique uses the purposive sampling method. The research results show that the sales cycle process carried out by PT Tunas Group Ridean is consistent with the Romney & Steinbart revenue cycle model. The implementation of internal control in PT Tunas Group's Ridean sales cycle is carried out holistically in accordance with the COSO IC framework. The activities in the internal control process on control environment, risk assessment, control activities, communication and information, and monitoring are carried out comprehensively and in accordance with the strategic objectives of PT Tunas Group Ridean.Keywords: Internal Control, COSO IC, Sales Cycle, Accounting Information System, Automotive Industry